2015
DOI: 10.1038/jcbfm.2015.180
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Vascular Remodeling after Endothelial Progenitor Cell Transplantation in MMP9-Deficient Mice Suffering Cortical Cerebral Ischemia

Abstract: Endothelial progenitor cells (EPCs) are being investigated for advanced therapies, and matrix metalloproteinase 9 (MMP9) has an important role in stroke recovery. Our aim was to determine whether tissue MMP9 influences the EPC-induced angiogenesis after ischemia. Wild-type (WT) and MMP9-deficient mice (MMP9/KO) were subjected to cerebral ischemia and treated with vehicle or outgrowth EPCs. After 3 weeks, we observed an increase in the peri-infarct vessel density in WT animals but not in MMP9/KO mice; no differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 17 publications
1
21
0
Order By: Relevance
“…40 Our results indicated that more EPCs were mobilized and migrated to the ischemic injury site after MMP-9-triggered glial scar degradation, and MMP-9 was essential for ischemiainduced neovascularization by either modulating bone-marrowderived EPCs or activating the VEGF signaling pathway. 39,41,42 How MMP-9 affected VEGFR2 and how EPCs regulated the formation of the vascular network after MMP-9 treatment in ischemic stroke need further investigation. Furthermore, EPC-secreted angiogenic cytokines, such as VEGF, hepatocyte growth factor (HGF), granulocyte colony-stimulating factor, and granulocyte-macrophage colony-stimulating factor, also played important roles.…”
Section: Discussionmentioning
confidence: 99%
“…40 Our results indicated that more EPCs were mobilized and migrated to the ischemic injury site after MMP-9-triggered glial scar degradation, and MMP-9 was essential for ischemiainduced neovascularization by either modulating bone-marrowderived EPCs or activating the VEGF signaling pathway. 39,41,42 How MMP-9 affected VEGFR2 and how EPCs regulated the formation of the vascular network after MMP-9 treatment in ischemic stroke need further investigation. Furthermore, EPC-secreted angiogenic cytokines, such as VEGF, hepatocyte growth factor (HGF), granulocyte colony-stimulating factor, and granulocyte-macrophage colony-stimulating factor, also played important roles.…”
Section: Discussionmentioning
confidence: 99%
“…EPCs are highly migratory and can home to target areas to regulate angiogenesis and vasculogenesis for tissue homeostasis or repair. In the context of central nervous system (CNS) injury and disease, EPCs may contribute to neurovascular recovery after stroke . However, the underlying mechanisms remain to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) are multipotent stem cells capable of self‐renew, differentiating, and participating in angiogenesis. Both MSCs and EPCs take part in vascularization and tissue repair and have been widely employed for cell‐based therapy in both preclinical studies and clinical trials .…”
mentioning
confidence: 99%